The influence of geometry of primary air channels in standard retort burners on dust emission - Ciupek Bartosz; Bartoszewicz Jarosław (MATEC Web of Conferences, 2019)
The article presents the analysis of dust emissions from a low power boiler fired with various solid fuels. The boiler, presented for testing, met the emission conditions for boilers made in the third class in accordance with the PN-EN 303-5: 2012 standard. The solid fuel boiler was equipped with two different retort burners with automatic fuel supply. For the test were used a first generation retort burner with a fixed rim and the next were used second generation retort burner provided with a rotary rim. Both constructions differ in the geometrical model of the primary air supply system to the furnace. During the tests, the work of the burners was controlled using a microprocessor temperature controller. During the research, the rotation time of the screw supplying the fuel through the retort to the furnace was changed, as well as the rotational speed of the blast fan impeller responsible for supplying the combustion air. The purpose of the tests was to check whether the boiler will meet the highest environmental class regardless of the technical parameters of the burner and fuel used. The article describes the research methodology and analysis of the results obtained. The effect of the tests carried out is a comparison of average dust emission values depending on the fuel used and the work settings of a given burner. The test results are a prerequisite for further research work in terms of the impact of primary air supply on the emission of harmful substances.